Estrogen receptor alpha and beta regulate actin polymerization and spatial memory through an SRC-1/mTORC2-dependent pathway in the hippocampus of female mice. Issue 174 (November 2017) - Zhao, Yangang; He, Li; Zhang, Yuanyuan; Zhao, Jikai; Liu, Zhi; Xing, Fangzhou; Liu, Mengying; Feng, Ziqi; Li, Wei; Zhang, Jiqiang
Graphical abstract: Highlights: Decreased mTORC2 signals are detected in the hippocampus of old mice. Levels of hippocampal SRC-1and mTORC2 are regulated by E2 and ERs' activity. SRC-1 knockdown regulates mTORC2 and actin polymerization, mTORC2 knockdown regulates actin polymerization. Activation of mTORC2 rescues ER antagonists induced actin depolymerization and spatial memory impairment. SRC-1/mTORC2 mediates ERs' regulation on actin polymerization and spatial memory. Abstract: Aging-related decline of estrogens, especially 17β-estradiol (E2), has been shown to play an important role in the impairment of learning and memory in dementias, such as Alzheimer's disease (AD), but the underlying molecular mechanisms are poorly understood. In this study, we first demonstrated decreases in E2 signaling (aromatase, classic estrogen receptor ERα and ERβ and their coactivator SRC-1), mTORC2 signaling (Rictor and phospho-AKTser473) and actin polymerization (phospho-Cofilin, Profilin-1 and the F-actin/G-actin ratio) in the hippocampus of old female mice compared with those levels detected in the adult hippocampus. We then showed that ERα and ERβ antagonists induced a significant decrease in SRC-1, mTORC2 signaling, actin polymerization, and CA1 spine density, as well as impairments of learning and memory; however, ovariectomy-induced changes of these parameters could be significantly reversed by treatment with ER agonists. We further showed that expression of SRC-1, mTORC2 signaling and actin polymerization could be upregulated by E2 treatment, and the effects of E2 were blocked by the ER antagonists but mimicked by the agonists. We also showed that the lentivirus-mediated SRC-1 knockdown significantly inhibited the agonist-activated mTORC2 signaling and actin polymerization, and the lentivirus-mediated Rictor knockdown also significantly inhibited the agonist-activated actin polymerization. Finally, we demonstrated that the ERα and ERβ antagonists induced a disruption in actin polymerization and an impairment of spatial memory, which were rescued by activation of mTORC2. Taken together, the above results clearly demonstrated an mTORC2-dependent regulation of actin polymerization that contributed to the effects of ERα and ERβ on spatial learning, which may provide a novel target for the prevention and treatment of E2-related dementia in the aged population.